Edukasi Literasi Ekonomi: Menanamkan Nilai dalam Aktivitas Menyenangkan - Irma Agusti; Siti Walida Mustamin; Juanda Astuti; Andi Dina Fadlia Mattoreang; Nurzahra; Ainun Nabila; Fitri Ramadani; Andi Gita Noviarsi; Evi Alfiani; Ivan Arba; Muh Rifkiadi Nasir (CV. ITTC INDONESIA, 2025)
Introducing financial literacy from an early age is a strategic step in shaping wise financial character in children. This outreach activity was carried out at Madrasah Ibtidaiyah Muhammadiyah, Parangmalengu, Gowa by a team of students from Muhammadiyah University Makassar. The methods used included initial observations, interactive presentations, discussions, and simple evaluations. The materials covered basic concepts of money, the importance of saving, and appropriate financial management techniques for elementary school-aged children. The results of the activity demonstrated high enthusiasm among the students and improved understanding of the value of saving and money management. Evaluation was conducted through questions and short quizzes, with prizes awarded as a form of motivation. This activity demonstrated that an enjoyable educational approach can enhance financial awareness from an early age. Moving forward, similar activities are expected to continue in order to cultivate a financially resilient younger generation capable of managing their finances wisely.